Bioactive Fish Scale Incorporated Chitosan Biocomposite Scaffolds for Bone Tissue Engineering - Kara, Aylin; Tıhmınlıoğlu, Funda; Tamburacı, Sedef; Kara, Aylin; Tıhmınlıoğlu, Funda; Havıtçıoğlu, Hasan (Elsevier Ltd., 2019)
Recently, biologically active natural macromolecules have come into prominence to be used as potential materials in scaffold design due to their unique characteristics which can mimic the human tissue structure with their physical and chemical similarity. Among them, fish scale (FS) is a biologically active material with its structural similarity to bone tissue due to including type I collagen and hydroxyapatite and also have distinctive collagen arrangement. In the present study, it is aimed to design a novel composite scaffold with FS incorporation into chitosan (CH) matrix for bone tissue regeneration. Therefore, two biological macromolecules, fish scale and chitosan, were combined to produce bio-composite scaffold. First, FS were decellularized with the chemical method and disrupted physically as microparticles (100 in), followed by dispersal in CH with ultrasonic homogenisation, CH/FS scaffolds were fabricated by lyophilization technique. Scaffolds were characterized physically, chemically, mechanically, and morphologically. SEM and porosity results showed that CH/FS scaffolds have uniform pore structure showing high porosity. Mechanical properties and degradation rate are enhanced with increasing FS content. In vitro cytotoxicity, proliferation and osteogenic activity of the scaffolds were evaluated with SaOS-2 cell line. CH/FS scaffolds did not show any cytotoxicity effect and the cells were gradually proliferated during culture period. Cell viability results showed that, FS microparticles had a proliferative effect on SaOS-2 cells when compared to control group. ALP activity and biomineralization studies indicated that FS micro particle reinforcement increased osteogenic activity during culture period. As a biological macromolecule with unique characteristics, FS was found as cytocompatible and provided promising effects as reinforcement agents for polymeric scaffolds. In conclusion, fabricated CH/FS bio-composites showed potential for bone tissue engineering applications. (C) 2019 Elsevier B.V. All rights reserved.
PubMed: 30797008
Keywords: Fish scale; CH; Composite scaffold; Bone tissue engineering